2012
DOI: 10.1152/ajpcell.00398.2011
|View full text |Cite
|
Sign up to set email alerts
|

Increased endogenous H2S generation by CBS, CSE, and 3MST gene therapy improves ex vivo renovascular relaxation in hyperhomocysteinemia

Abstract: Hydrogen sulfide (H2S) has recently been identified as a regulator of various physiological events, including vasodilation, angiogenesis, antiapoptotic, and cellular signaling. Endogenously, H2S is produced as a metabolite of homocysteine (Hcy) by cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE), and 3-mercaptopyruvate sulfurtransferase (3MST). Although Hcy is recognized as vascular risk factor at an elevated level [hyperhomocysteinemia (HHcy)] and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 63 publications
(69 reference statements)
1
87
0
1
Order By: Relevance
“…The main physiological role of CBS is to metabolize homocysteine. Thus, we predict that treatment with any pharmacological CBS inhibitor will be associated with some accumulation of plasma homocysteine, a known cytotoxic molecule and cardiovascular risk factor (12,24,27,50,104). Accordingly, CBS knockout animals have a limited life span, which is a consequence of severe hyperhomocysteinemia (3,74).…”
Section: H 2 S Donation Versus H 2 S Biosynthesis Inhibition In Cancermentioning
confidence: 99%
“…The main physiological role of CBS is to metabolize homocysteine. Thus, we predict that treatment with any pharmacological CBS inhibitor will be associated with some accumulation of plasma homocysteine, a known cytotoxic molecule and cardiovascular risk factor (12,24,27,50,104). Accordingly, CBS knockout animals have a limited life span, which is a consequence of severe hyperhomocysteinemia (3,74).…”
Section: H 2 S Donation Versus H 2 S Biosynthesis Inhibition In Cancermentioning
confidence: 99%
“…The mitochondrial enzyme 3-mercaptopyruvate sulfurtransferase (3-MST) is a newly identified endogenous source of hydrogen sulfide (H 2 S) in various cells and tissues, including vascular endothelial cells (17)(18)(19). We have recently demonstrated that 3-MST activity is inhibited by oxidative stress in vitro and speculated that this may exert adverse effects on cellular homeostasis (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Cystathionine beta-synthase (CBS) and 3-mercaptopyruvate sulfurtransferase (3MST) also have been reported to contribute to the endogenous generation of H 2 S in vascular cells (34,35). The effects of H 2 S in the vascular system are complex and permit H 2 S to exert a wide range of actions, including vasodilatation, angiogenesis, cellular bioenergetics, and energy production (13,38,39).…”
Section: Introductionmentioning
confidence: 99%